Application of HEC-RAS in 2D Dam Break Simulation-A Case Study of Hongqi Reservoir - HUANG Binbin; GE Liming; XU Xian; WANG Yue (Renmin Zhujiang)
This paper simulates the dam break of Hongqi reservoir by HEC-RAS software,studies the discharge hydrograph of breach,the local flow pattern downstream of the breach,the propagation of dam break flood wave in flood area and the life loss caused by dam break flood,discusses the distribution of flood velocity and flood inundation depth,and draws the risk map of inundation depth.After analysis of the discharge hydrograph of breach,it is found that the larger the instantaneous breach size is,the greater the initial discharge is,and the faster the initial discharge hydrograph changes,while the smaller the breach size is,the slower the discharge hydrograph changes.Based on the evaluation of life loss caused by dam break flood,the loss of life and its severity coefficient are lower when the alarm time is longer.When there is no alarm,the life loss reaches 210.When the alarm time is 1 hour,the loss of life is obviously reduced,and the life loss is 0 when the alarm time is 3.5 hours.